Double osteotomies with iliac crest bone allograft and distal fibular autograft to correct a severe pediatric ankle varus deformity: A case report - Lily Nguyen, DPM; Brian B. Nielsen, MD (Foot & Ankle Surgery: Techniques, Reports & Cases)
Ankle varus can occur after a distal tibial fracture or a physis injury in the pediatric population, can be debilitating for these children as the deformity progresses. Severe ankle varus deformities in pediatric patients pose significant challenges in orthopedic and podiatric surgery. These deformities often impair ambulatory function, lead to pain, and increase the risk of joint degeneration if left untreated. There are a few literature reports on the surgical treatment for ankle varus in children, but none on a single-stage correction with double osteotomies with iliac crest graft and fibular autograft. This case report presents on a 13-year-old patient who underwent double osteotomie with the use of an iliac crest bone allograft and distal fibular autograft to correct a severe acquired ankle varus deformity. The patient sustained a Salter-Harris type III at the age of 8, underwent percutaneous reduction internal fixation for medial malleolar fracture, and went on to develop varus deformity with a premature asymmetrical growth plate. On plain radiography, the Tibial-Ankle Surface (TAS) angle was at 57°. He was elected for a single-stage closing wedge fibular osteotomy, opening wedge tibial osteotomy with bone grafts and internal fixation, and Achilles tendon lengthening as an adjunct procedure to correct the equinus which presented after the double osteotomies. After the correction, the mechanical axis deviation improved by 34.3 mm and the post-op TAS measured 89°.